Analisis Wacana Kritis Teun A. Van Dijk pada Program Acara Newscast Isu Penundaan Pemilu 2024 - Mia Sanita Siagian; M. Surip; Syairal Fahmy Dalimunthe (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This article discusses Teun's discourse analysis. A Van Dijk, namely social cognition. The discourse discusses the issue of postponing the 2024 election. The method used in this study is a qualitative descriptive method with the observation method as a data collection method. This descriptive qualitative research is used to describe the results of data collection that has been carried out by researchers through interviews and observations. The approach used in this study is a qualitative approach. Qualitative descriptive design is used to obtain a clear, objective, systematic picture. The object of this research is the discourse that appears in the Newscast program for the heated debate on allegations of postponing the 2024 election. The critical discourse analysis of Teun A. van Dijk analyzes text analysis, social cognition, and social context. The result of this research is that in macro structure, super structure, and microstructure, discourse can be used as a means to shape the speaker's opinion through the right choice of words, sentence structure, and style.